Promotion of Robusta Coffee Agrotourism in Pagar Alam City, South Sumatra - Umi Narimawati; M. Yani Syafei; Ahmad Feriyansyah; Yadi Maryadi (International Journal Of Community Service, 2025)
This community service activity aims to enhance the promotion of Robusta Coffee agrotourism potential in Pagar Alam City, South Sumatra Province, as one of the leading destinations focusing on agriculture and ecotourism. Through a participatory and collaborative approach involving coffee-based Micro, Small, and Medium Enterprises (MSMEs), farmers, and village tourism authorities, the program included training in digital marketing, the creation of promotional content, and strengthening local coffee identity. The results of this activity demonstrate an increased understanding among local actors regarding branding strategies, optimization of social media content creation skills, and an expansion of digital-based promotional outreach. This program is expected to strengthen tourism appeal and support sustainable local economic growth rooted in Robusta coffee.